Modern Education Management: Challenges, Strategies Towards a Future of Continuing Education - Basri, Hasan; Nurhayuni; Hasri, Salfen; Sohiron (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2024)
In an era of ever-changing education, educational management has an important role in facing various challenges, technological advances, and societal developments. This article aims to explore the significant changes in education today, analyze the main challenges faced by modern educational management, and detail innovative strategies that can be used to achieve a sustainable educational future. This research method uses a qualitative approach by conducting in-depth research to identify the main trends in management education. The research results show a need for adaptive leadership, technology integration, improving teaching quality, and educational inclusion to create a sustainable educational environment. The conclusion of this article emphasizes that effective educational management and a focus on innovation are the keys to overcoming rapid changes in the world of education and achieving sustainable educational goals. Through this approach, education management can prepare to overcome challenges and design strategies that make education more relevant, inclusive, and sustainable.